Morphological Types of Anemia Associated with Chronic Renal Diseases - Mohammed, Mazin Razooqi; Mahmood, Bushra (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Anemia develops early in the course of renal disease and worsens as kidney function declines; a typical consequence of CKD is caused by a disruption in erythropoietin production as well as caused by iron and vitamin shortages, blood loss, shortened erythrocyte life span, chronic inflammation, and the uremic environment. Aim: Our study aimed to identify and classify different types of anemia that complicated patient with chronic kidney disease. Methods: 40 patient were included in this study, 32 males (80%) and 8 females (20%), the age range was 40-70 for male and 48-68 for female .Depending on clinical sign, symptoms and laboratory diagnostic test All those patient are diagnosed previously as a cases of chronic renal failure by clinicians in our city and develop anemia during the course of diseases, so clinicians referred patients to our laboratory to find the cause of anemia. Depending’s on hematological laboratory data, peripheral blood smear examination from these 40 patients, which showed different types of anemia. Results: the most common types of anemia was Normochromic anemia (62.5 %) which develop in 25 patients followed by hypochromic microcytic anemia (8 %) which develop in 8 patients, and followed by macrocytic anemia (12.5 %) which develop in 5 patients and the less common type of anemia was hemolytic anemia (5 %) which was founded in 2 patients.. Conclusion: All types of anaemia can be detected in-patient with different types of renal diseases and it’s important to used different type of laboratory test to diagnosed type of anemia to treat it.